Efficiency enhancement of perovskite solar cells by designing GeSe nanowires in the structure of the adsorbent layer. (28th August 2020) - Aliyariyan, Masoud; Fathi, Davood; Eskandari, Mehdi; Tooghi, Alireza
Abstract: In this paper, coupled optical and electrical simulations of perovskite solar cells (PSCs) are performed to optimize their basis output parameters and obtain the best power conversion efficiency (PCE) based on both the light absorption and carrier transport mechanisms. Due to the limitations of perovskite absorption in longer wavelengths, we used an extra photo-active material of GeSe with a narrower bandgap and a broader absorbing spectrum to increase the efficiency of the PSC. To prevent carrier transmission disorder that exists in the planar structure with two absorbing materials, GeSe was inserted into the main active layer in the form of nanowires (NWs). As a result, it improved the carrier transfer and open-circuit voltage ( Voc ) in addition to the short-circuit current density ( Jsc ). The behavior of PSC with different sizes of GeSe NWs at the same density was investigated to determine the appropriate size of NWs and achieve the highest PCE. In the optimal structure with 50 nm diameter NWs, Jsc and PCE of the cell are 22.96 mA cm −2 and 18.97%, which are improvements of 39% and 50%, respectively, compared to the planar structure studied at the beginning of the paper.